Alopecia areata. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 1. Diagnosis and severity assessment - Adriana Rakowska; Lidia Rudnicka; Małgorzata Olszewska; Beata Bergler-Czop; Joanna Czuwara; Ligia Brzezińska-Wcisło; Joanna Narbutt; Waldemar Placek; Barbara Zegarska (Termedia Publishing House, 2023)
The existence of two types of alopecia areata is suggested (probably genetically different): early-onset, with more severe symptoms, longer disease duration, higher tendency to relapse, often with a positive family history, and late-onset, in which the first symptoms occur after the age of 50, the course is milder and the family history is negative. Alopecia areata may exist in the form of: focal alopecia areata, multifocal alopecia areata, ophiasis, diffuse alopecia areata, alopecia totalis and alopecia universalis. Alopecia areata incognita remains a form with a discussed relationship to alopecia areata. Occasionally hair loss associated with alopecia areata may occur only in locations outside the scalp (e.g. beard, eyebrows, eyelashes, body hair). The diagnosis of alopecia areata can be made on the basis of clinical examination and trichoscopy. There are two main scoring systems for assessing the severity of alopecia areata. This is the Severity of Alopecia Tool (SALT) and the Alopecia Areata Score (AAS), which is also partly based on the SALT assessment. Both scoring systems allow differentiation between mild, moderate, and severe alopecia areata. These assessment results have a direct impact on therapeutic decisions.